Factors influencing brand equity: Testing Aaker’s brand equity framework in Malaysian toy industry - Wong Chee Hoo; Chai Yi Xin; Visal Moosa (Innovative Marketing, 2024)
Previous studies have demonstrated varying associations between fundamental components of brand equity within diverse sectors. The purpose of the current study is to examine the influence of Aaker’s brand equity model’s dimensions (brand awareness, brand loyalty, perceived quality, and brand association) on brand equity in the context of toy brands in Malaysia. The study employs a quantitative-based correlation design within a non-controlled setting, using a cross-sectional approach with individuals as the unit of analysis. The population consists of respondents from the general public aged 18 and above, as they are valid buyers of toys. Data collection was conducted using a non-probability sampling method. The questionnaire was sent to the targeted respondents using online Google Form links. A comprehensive dataset from 384 respondents was gathered for descriptive analysis of the demographic profile. Hypothesis testing was performed using regression analysis. The findings indicate that, except for brand associations, the remaining three factors – perceived quality (Beta = .377, p < .001), brand loyalty (Beta = .338, p < .001), and brand awareness (Beta = .221, p < .01) – exhibit a statistically significant positive correlation with the brand equity of children’s toy brands in Malaysia. AcknowledgmentThe authors thank INTI International University, Malaysia, for providing financial support to publish this paper.